Recent Developments in Palm Fibers Composites: A Review - Alhijazi, Mohamad; Zeeshan, Qasim; Safaei, Babak; Asmael, Mohammed; Qin, Zhaoye (Springer, 2020)
There is a growing interest in the development of natural fiber composites (NFC), alternate to the existing artificial fiber composites. In recent years, the application of natural fibers as reinforcement in composite structures has received increasing attention due to their advantages of low cost, environmental friendliness and favorable biocompatibility over synthetic fiber composite materials. Every year, palm harvesting generates tons of biomass wastes around the globe, whereas these fibers have the potential to be recycled and involved in the development of palm natural fibers composites (PNFC). This paper presents a review on the recent developments in palm natural fibers composites. Various palm types and their extracts such as sugar palm, oil palm, date palm, and peach palm are included in the review. Furthermore, their physical, mechanical, morphological, electrical, and thermal properties are reviewed. It is observed that palm fibers can be applied with a variety of resins like epoxy, polyester, polypropylene, and high-density polyethylene since these PNFCs reveal a set of remarkable characteristics.
Keywords: Natural fibers composites; Palm fibers; Mechanical properties; Physical properties; Thermal properties